PERILAKU KREATIF DAN INOVATIF KEWIRAUSAHAAN MAHASISWA DALAM USAHA PRODUKSI POTATO CHEESE STICK DI MEDAN SUNGGAL - Sri Arpaini; Haidir Lubis (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this research is to innovate new snacks with potato-based ingredients and to train students' independence and creativity. Potato cheese stick business was established at Warung Kak Fay, Medan Sunggal District, Medan City. This place was chosen because it is a strategic location which is beside a main road so that many people pass it. The promotion methods used are personal selling and internet marketing. The results of this study, namely the potato cheese stick business can achieve a profit of Rp. 15,960,000/month assuming all the potato cheese stick products produced (50 pcs/day) are sold out.